Vitrification of U3O8 in iron aluminium phosphate matrices including Bi2O3 as uranium surrogate - Rincón, J. Ma. (2018)
In order to encapsulate nuclear wastes (NW) enriched in Uranium, they have been designed and obtained vitrified matrices of iron aluminum phosphates including substitution of U by Bi. These glasses have been designed and obtained formulating all from the starting binary composition: 60P2O5·40Fe2O3 where the Fe/P ratio was 0.67. The thermal behavior has been investigated by DTA/TG analysis and thermal expansion, as well as identification of some phases by TEM/EDS. The vitrified structures are difficult to crystallize as is the case of the (Fe + U) contents in the range of 0.50 per P atom. Glasses with Bi-oxide are less resistant to crystallization than those containing U. The glasses here investigated depict a reasonable water chemical stability due to the high percentage of P–O–Fe–O bonds and the presence of U (4+ to 6+). Lately, it has been also investigated the calcination of simulated miniplates of Si2U3/Al having additions of these glasses and U3O8 to dilute this Uranium enriched in MTR combustible (Material Testing Reactor).